A inserção da zona costeira nas territorialidades da bacia hidrográfica do Rio São João - RJ: inter-relações, trocas e conflitos - Barros, Sergio Ricardo da Silveira (2007)
The space is product, process and manifestation of the society, where if the contradictions of the social relations of production express all. When the hydrographical basins and the coastal zones are about the ambient questions, mainly in extremely complex environments as, are necessary to undertake an integrated plan of management, being indispensable that they make it in participative way, involving one diversified group to know, trying to the maximum to establish connector links polidisciplinares and multidimensional. The coastal zone can be considered a macro geo-ambient system, formed in the area of direct interaction enters the domain of the ocean and the terrestrial, composed dominions for different landscapes, sheltering an ecosystem diversity of high fragility requiring, therefore, special attention of the public power and the society, being inserted in the Brazilian Federal Constitution as area of national patrimony. Being represented for complex units, consisting of inter-relations between its systems. The area of study of this work is the Coastal Zone of the Hydrographic Basin of the River São João, who understands the space of influence of its continental and oceanic system, being considered a typical example of appropriation of the spaces natural, determined for the imposition of a culture that if relates with the nature for the value of exchange and not for its use. To manage the modifications of the multiple landscapes of the coastal hydrographical basins consists one of the great challenges faced for the most diverse sectors of the organized society, mainly those that use the existing natural resources in these areas. The task still more becomes complex if to consider that these areas are citizens the changes of diverse magnitudes. However, the compatibilização of the management of the coastal zone with the management of hydrographical basins blunts as a great challenge, requiring the composition of the legal, administrative, institutional aspects, technician. The plan of management for the coastal zone presents a mapping of the main problems and a plan of action to mitigate them. The main conflicts are related to the historical process of formation of the coastal space of the basin, having been necessary a coastal ecological-economic zoning aiming at to integrate and to command these spaces to the uses. This work has as objective to consider subsidies for a plan of management for the Coastal Zone of the Hydrographic Basin of the River São João, evaluating the inter-relations, interactions and conflicts with the management of the hydrographical basin, making compatible the multiple uses of the coastal spaces and its basin of draining, searching to command them in sustainable bases, through techniques of economic-ecological zoning, aiming at the development local.